Organizational Innovation by Integrating Simplification : Learning from Buurtzorg Nederland - Nandram, Sharda S. (Management for Professionals,, 2015)
This book presents the theory of integrating implification and it provides a profound evidence based study of Buurtzorg Nederland. The case itself, forming the building block of the theory, has received tremendous interest in the Netherlands and abroad. This is the first international book on Buurtzorg Nederland and the first one departing from a management multidisciplinary perspective. The book demonstrates theory building by using the Grounded Theory Methodology as a way to contribute to management theory. Integrating simplification gives room for context specific implementation of organizational innovation to different industries. One of the most talked about and innovative cases in community care: the successful and award winning practice of Buurtzorg. There is only one simple focus: the wellbeing of the client. Prof. Dr. Mathieu Weggeman, the Netherlands All grounded theories are asymptotic, that is as close to perfection as possible. Sharda has come very close to achieving a perfect Grounded Theory.  Read well and enjoy the conceptual level and integration of concepts! Barney G. Glaser, PhD, Hon. PhD, USA Integrating Simplification Theory shows in a lucid and convincing way, how constructing reality based on different sources and processes of knowledge results in new organization creation. Prof. Ikujiro Nonaka, Japan Sharda has seamlessly combined the Eastern and Western philosophies to explain human principles of organizing the reality around us. The book has truly brought out the "art of management". Dr. Madhumita Chatterji, India The humanistic leadership of Buurtzorg demonstrates the Yoga philosophy which transcends the duality of matter and spirit as well as the duality of self and others, leading to radical simplicity. Sharda has provided a fascinating analysis of a fascinating case. Prof. Laszlo Zsolnai, Hungary  .